(untitled) (Sustainability in Debate, 2019)
The Environmental Protection Area of Pirineus (EPA) extends over 22,800 hectares around Pireneus Park - GO Park, bordering the cities of Pirenópolis, Cocalzinho de Goiás and mountainous areas of Corumbá de Goiás. The aim of the study was to verify if the municipalities bordering the EPA of Pirineus have benefited from these protected areas, providing local growth and development. This is a bibliographical, qualitative and documentary research. The satellite images Landsat-5 e Landsat-8 extracted from the catalog at Inpe’s General Imaging Division, were used to the classification of land use and occupation in EPA, and to characterize the impact of the area were used the method of Oldekop et al. The results are presented descriptively and analytically. The creation of the Conservation Units of Pirineus, in addition to changing the socio-cultural context of the region, contributed to the population growth on average 11,46%, the displacement of this to rural area in 27% in Cocalzinho, a 51% average increase in per capita income and an increase in development rates, such as a 30% increase in the HDI.